Synthesis and Photocatalytic Degradation of Water to Produce Hydrogen from Novel Cerium Dioxide and Silver-Doped Cerium Dioxide Fiber Membranes by the Electrospinning Method - Pu, Xingyu; Wang, Chencheng; Chen, Xingwang; Jin, Jing; Li, Wanfei; Chen, Feng (Frontiers in Materials, 2021)
The sol-gel method combined with electrospinning technique were used to synthesize the CeO2 nanofiber membranes and CeO2 fiber membrane doped with different contents of nano-silver. The thermal degradation behavior, phase structure, morphology, optical and photocatalytic hydrogen production efficiency of CeO2 nanofiber membranes and CeO2 fiber membrane doped with different contents of nano-silver were studied. XRD results indicate that the increase of silver concentration can inhibit the formation of CeO2 crystal. SEM and TEM observation shows that the prepared CeO2 with diameter of about 100 nm and fiber membrane material doped with nano silver, the fiber is made of a large number of grain accumulation. Analysis of optical properties found that the doped nano – silver CeO2 fiber membrane enhances the absorption of visible light and reduces the band gap of the material. Photocatalytic experiments show that the cerium dioxide nanofibers doped with nano-silver can greatly improve the photocatalytic performance of materials than that of pure CeO2. The Ag / CeO2 fiber membrane with the Ag / CeO2 molar ratio of 3:50 possess highest photocatalytic hydrogen production efficiency because of its high electron hole transfer and separation efficiency. This novel synthesis strategy can be used to prepare other broad band gap semiconductor oxides and enhance their photocatalytic activity.